Integrated Schools Teachers’ Knowledge and Skills on Classroom-Based Action Research: Basis for Community Extension Program - Kimberly C. Rivera; Leandro T. Olubia; Normita M. Lugtu; Romeo T. Quintos (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study. This study explored the competence and training needs of integrated school teachers in conducting Classroom-Based Action Research (CBAR), aiming to design a Community Extension Program that enhances their research capability. Methodology. A Sequential Explanatory Mixed-Methods Design (QUAN → qual) was employed with 62 integrated school teachers from Balanga City, Bataan, Philippines. Data were gathered using a validated CBAR Competence and Training Needs Questionnaire, followed by semi-structured interviews with selected participants. Descriptive statistics, non-parametric tests, and thematic analysis were used to analyze the data. Main Findings. Results showed that teachers demonstrated moderate competence in selecting a research focus (M≈2.64) and collecting data (M≈2.51), while they found analyzing and interpreting results (M≈2.39) and translating findings into action (M≈2.41) more challenging. Training needs were highest in statistical analysis (M≈3.57) and literature synthesis (M≈3.73). Teachers expressed strong willingness to conduct CBAR but identified areas where additional technical support, confidence-building, and institutional backing would be helpful. Novelty/Originality of this study. Unlike most CBAR research in the Philippines that focuses on general public-school teachers, this study examines teachers from integrated schools in Balanga City, Bataan, Philippines, a unique context where educators handle multi-level and multi-subject responsibilities. This localized focus identifies the importance of strengthening research competence in schools with complex instructional settings. The study contributes by proposing a structured, year-long CBAR Capability-Building Program aligned with teachers’ identified needs.